Multicast for small conferences a scalable multicast mechanism on IPv6. - Egger, S. (IEEE Communications magazine)
Many new Internet applications require data transmission from a sender to multiple receivers. Unfortunately, the IP multicast technology used today suffers from scalability problems, especially when used fro small and sparse groups. Multicast for small conferences (MSC) is a novel approach aimed at providing more efficient support for audio conferences, for example. It makes use of an IPv6 routing header. The unicast addresses of a small receiver group are put into the extension header in order to be forwarded to all group members. The results indicate that MSC has the potential to replace IP multicast for many delay-sensitive small group applications, even with very limited support from the network infrastructure.